2017
DOI: 10.1039/c7cp01614j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oxygen-release/storage properties of Pd-loaded Sr3Fe2O7−δ

Abstract: This study proves that a small amount of Pd loading (1 wt%) on SrFeO can dramatically enhance the oxygen-storage properties of SrFeO. The topotactic oxygen intake and release between SrFeO and SrFeO takes place in response to gas switching between an O flow and H flow, regardless of the presence or absence of Pd loading. The effect of Pd loading is significant for the oxygen-release process under H atmosphere; that is, highly dispersed Pd metal nanoparticles sized less than 1 nm formed on Pd/SrFeO to promote H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…S6). The catalytic influence of a noble metal on redox of perovskite was noted by Beppu et al [27], when the impregnation of 1 wt% of Pd onto Sr3Fe2O7 significantly enhanced its oxygen release and storage. The results in Fig.…”
Section: Materials Characterisationmentioning
confidence: 86%
“…S6). The catalytic influence of a noble metal on redox of perovskite was noted by Beppu et al [27], when the impregnation of 1 wt% of Pd onto Sr3Fe2O7 significantly enhanced its oxygen release and storage. The results in Fig.…”
Section: Materials Characterisationmentioning
confidence: 86%
“…To satisfy such strict requirements, reasonably good structural stability and proper ionic conductivity must be balanced because a higher structural stability could reduce the mobility of oxygen ions and vice versa. Many perovskite-related materials have been explored in previous research. Among them, the family of Ruddlesden–Popper A n +1 B n C 3 n +1 oxides has been studied for use in ionic-conducting applications, such as SOFCs and oxygen-storage materials, operating at intermediate or high temperatures (300–900 °C). In particular, Sr 3 Fe 2 O 7−δ , which contains no rare-earth elements, has recently been found to exhibit high structural stability and high oxygen-ion conductivity. , Beppu et al revealed that Sr 3 Fe 2 O 7−δ shows higher performance in the oxygen storage capacity and the rate of oxygen release and storage, compared with the conventional Pt/Ce 2 Zr 2 O 8 used in three way catalysts . It is also experimentally shown that Sr 3 Fe 2 O 7−δ is more sustainable under H 2 reductive conditions than perovskite SrFeO 3−δ .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported that Sr 3 Fe 2 O 7−δ , with a layered perovskite-type structure, exhibits topotactic oxygen-storage/release behaviors and has higher structural stability under severe reductive condition than SrFeO 3−δ . , The space group ( I 4/ mmm ) of Sr 3 Fe 2 O 6.75 is identical to that of Sr 3 Fe 2 O 6 obtained through the release of lattice oxygen. Only oxygen ions at the apical position between bilayers of FeO 6 in Sr 3 Fe 2 O 6.75 are topotactically eliminated by reduction with H 2 (Figure ) because the oxygen vacancy site at the apical position is more stable than that at the equatorial position in Sr 3 Fe 2 O 6.75 .…”
Section: Introductionmentioning
confidence: 88%
“…X-ray absorption fine structure (XAFS) spectra at the Fe, Mn, Co, and Ni K-edges were measured at the BL11S2 beam line of the Aichi Synchrotron Radiation Center (AichiSR); these spectra were recorded in transmission mode at room temperature using a Si(111) double-crystal monochromator. Time-resolved in situ energy-dispersive XAFS (DXAFS) spectra at the Sr K-edge were measured with a polychromator in transmission mode at the BL28B2 beam line of SPring-8, as described in our previous reports. , Each sample (30 mg) was pressed into a pellet and placed in a batch-type in situ cell. The sample was pretreated with pure H 2 at 873 K for 15 min and then with pure O 2 under the same conditions.…”
Section: Methodsmentioning
confidence: 99%